Ecological, historical and evolutionary determinants of modularity in weighted seed‐dispersal networks. (28th January 2014) - Schleuning, Matthias; Ingmann, Lili; Strauß, Rouven; Fritz, Susanne A.; Dalsgaard, Bo; Matthias Dehling, D.; Plein, Michaela; Saavedra, Francisco; Sandel, Brody; Svenning, Jens‐Christian; Böhning‐Gaese, Katrin; Dormann, Carsten F.; et al.
Abstract Modularity is a recurrent and important property of bipartite ecological networks. Although well‐resolved ecological networks describe interaction frequencies between species pairs, modularity of bipartite networks has been analysed only on the basis of binary presence–absence data. We employ a new algorithm to detect modularity in weighted bipartite networks in a global analysis of avian seed‐dispersal networks. We define roles of species, such as connector values, for weighted and binary networks and associate them with avian species traits and phylogeny. The weighted, but not binary, analysis identified a positive relationship between climatic seasonality and modularity, whereas past climate stability and phylogenetic signal were only weakly related to modularity. Connector values were associated with foraging behaviour and were phylogenetically conserved. The weighted modularity analysis demonstrates the dominating impact of ecological factors on the structure of seed‐dispersal networks, but also underscores the relevance of evolutionary history in shaping species roles in ecological communities.